2021
DOI: 10.3389/fphar.2020.624710
|View full text |Cite
|
Sign up to set email alerts
|

Ethnomedicinal Plants of Hasankeyf (Batman-Turkey)

Abstract: Hasankeyf is an ancient city, dating back to more than 10,000 years, in the Southeast Anatolia Region of Turkey. The area is separated by the Tigris River on both sides and located in the Batman province. However, as a result of a dam project, in February 2020, this ancient city and some of its surrounding villages were totally flooded. The residents were moved to new settlements. This study aimed to prevent the possible loss of ethnomedicinal knowledge of plants due to migration as well as to pass on this kno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 50 publications
(71 reference statements)
0
7
0
Order By: Relevance
“…When I compared plant usage data from Güce with that from previous studies of the Colchic sector (including Georgia), I found that medicinal plant usage in Güce was most similar to that in Espiye (Giresun) ( Polat et al., 2015 ) and least similar to that in north-eastern Anatolia ( Sezik et al., 1991 ). These similarities are expected as Espiye is adjacent to Güce and shares the same ecosystems ( Yeşil and İnal, 2021 ). One reason that Güce and north-eastern Anatolia show low similarity in plant usage may be related to the traditional data obtained from the areas belonging to the Irano-Turanian (outside the Circumboreal phytogeographical region) phytogeographical region.…”
Section: Resultsmentioning
confidence: 71%
See 1 more Smart Citation
“…When I compared plant usage data from Güce with that from previous studies of the Colchic sector (including Georgia), I found that medicinal plant usage in Güce was most similar to that in Espiye (Giresun) ( Polat et al., 2015 ) and least similar to that in north-eastern Anatolia ( Sezik et al., 1991 ). These similarities are expected as Espiye is adjacent to Güce and shares the same ecosystems ( Yeşil and İnal, 2021 ). One reason that Güce and north-eastern Anatolia show low similarity in plant usage may be related to the traditional data obtained from the areas belonging to the Irano-Turanian (outside the Circumboreal phytogeographical region) phytogeographical region.…”
Section: Resultsmentioning
confidence: 71%
“…Although there are modern health facilities in the center of Güce, old people, unlike younger people, are reluctant to visit those facilities. In addition, knowledge and the number of medicinal plants cited increases with age, among both male and female informants ( de Albuquerque et al., 2011 ; Gaoue et al., 2017 ; Nguyen et al., 2020 ; Yeşil and İnal, 2021 ). In Güce, illiterate informants have more ethnobotanical knowledge, likely because they live in harmony with nature.…”
Section: Resultsmentioning
confidence: 99%
“… [ 75 ] Turkey Leaves are used to cure diarrhoea, diabetes, headache, ulcers, urinary disorders, wounds and constipation. [ 76 , 77 , 78 ] Australia Australia Aerial parts are eaten to cure scurvy, irritations, inflammations and as a diuretic and antibiotic agent. [ 15 ] Africa Algeria It is used against dyspepsia and also as a diuretic.…”
Section: Ethnomedicinal Importance Of Purslanementioning
confidence: 99%
“…There are also clues regarding use of purslane for respiratory diseases in ancient Iranian medical books [ 179 ]. Ethnobotanical studies suggest that it has been an important part of traditional medicine among various cultures in different parts of this world [ 71 , 78 , 93 , 96 ]. The qualitative and quantitative analysis of phytochemical composition also supports its pharmacological value.…”
Section: Ethnopharmacological Potential Of Purslanementioning
confidence: 99%
“…Although traditional medicine is used for primary health care by about 80% of the world's population, for centuries, medicinal plants have been used to treat a wide range of ailments all over the world. In fact, over fifty thousand of the world's estimated 422.000 plant species are used for medicinal purposes (Hamilton, 2004;Yeşil and İnal, 2021).…”
Section: Introductionmentioning
confidence: 99%